1997
DOI: 10.1007/bf00434095
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after pelvic ring injuries: follow-up results of a prospective study

Abstract: A follow-up after 2 years on average could be done in 43 cases of pelvic ring injuries. Seven were type A, 8 type B and 28 type C lesions. Every type A lesion was treated non-operatively. External fixation and non-operative management were used with type B injuries. As well as non-operative treatment, both internal and external surgical techniques were employed for type C fractures. While group A hardly mentioned pain in the follow-up, groups B and C suffered dorsal pelvic pain of comparable intensity irrespec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 5 publications
3
7
1
5
Order By: Relevance
“…However, our findings were LC type injury was least likely and VS type most likely to result in sexual dysfunction, with similar findings for urinary dysfunction. These findings are supported by a previous German study [28] using the Tile classification [40], which reported higher rates of sexual dysfunction in Type B1 than B2 fractures and in Type C than B2 injuries, as well as other studies showing greater instability associated with more sexual complaints and less recovery [16,28,29,34]. However, there are conflicting reports, with other studies finding no apparent relationship of pelvic fracture type and sexual dysfunction in males [25,31] or females [3,9,11].…”
Section: Discussionsupporting
confidence: 74%
“…However, our findings were LC type injury was least likely and VS type most likely to result in sexual dysfunction, with similar findings for urinary dysfunction. These findings are supported by a previous German study [28] using the Tile classification [40], which reported higher rates of sexual dysfunction in Type B1 than B2 fractures and in Type C than B2 injuries, as well as other studies showing greater instability associated with more sexual complaints and less recovery [16,28,29,34]. However, there are conflicting reports, with other studies finding no apparent relationship of pelvic fracture type and sexual dysfunction in males [25,31] or females [3,9,11].…”
Section: Discussionsupporting
confidence: 74%
“…In one prospective study including 28 Type C lesions, no or slight pain was present in 50% of patients, moderate pain was present in 43%, and severe pain was present in only 7% [7]. However, half of all patients in this group had to change their profession because of their pelvic ring injuries [7]. Comparable findings were reported by Pohlemann et al [27], with a followup of 21 patients with Type C injuries.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, we believe the short operative duration and marginal blood loss are advantages of the TIFI. In one prospective study including 28 Type C lesions, no or slight pain was present in 50% of patients, moderate pain was present in 43%, and severe pain was present in only 7% [7]. However, half of all patients in this group had to change their profession because of their pelvic ring injuries [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations